A polyamide composite material and its preparation method and application

By adding polyamide with specific amino group values ​​and epoxy resin with specific epoxy values ​​to the polyamide, a polyamide composite material that is easily coated with soft glue is prepared, which solves the problem of poor bonding effect between soft glue and hard glue in the prior art, and significantly improves the adhesive properties of the material.

CN116355403BActive Publication Date: 2025-03-18KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111620861.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-28
Publication Date
2025-03-18
Estimated Expiration
2041-12-28

AI Technical Summary

Technical Problem

It is difficult to develop a polyamide composition with excellent coverability in the prior art, resulting in poor bonding effect between soft glue and hard glue, and easily lead to abnormalities such as degumming.

Method used

A polyamide composite material that is easily coated with soft glue is prepared by adding polyamide with a specific amino group value and an epoxy resin with a specific epoxy value to the polyamide, combined with fillers and additives. The material is extruded and granulated by a twin-screw extruder. The screw cylinder temperature range is 180-300℃, the screw length-to-diameter ratio is 36~52:1, and the rotation speed is 200-700rpm.

Benefits of technology

The bonding effect between polyamide composite materials and conventional polyamide adhesive soft glue is significantly improved, the adhesive properties of the material are enhanced, and the occurrence of degumming is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a polyamide composite material, which comprises the following components by weight: 100 parts of polyamide with a terminal amino value of 45-200 mmol / kg, and 0.1-8 parts of epoxy resin with an epoxy value of 0.03-0.3. The present invention can significantly improve the coating property of the polyamide composite material by soft glue (TPE, TPV, TPU, etc.) by adding epoxy resin with a specific epoxy value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a polyamide composite material and a preparation method and application thereof. Background Art

[0002] Modified polyamide has excellent comprehensive properties such as good mechanical properties, chemical resistance, and heat resistance, so it is widely used in internal load-bearing parts or shell parts in industries such as rail transportation, consumer appliances, power tools, and shared bicycles. Especially when used as shells for power tools and security components, a design of soft glue (such as TPE, TPV, TPU, etc.) covering hard glue (reinforced polyamide or filled reinforced polyamide) is often used. The production process is often to first injection mold the hard glue part, and then use secondary injection molding to cover the soft glue on the hard glue.

[0003] The form of soft glue covering hard glue, on the one hand, protects the hard glue, making the product have better impact and drop resistance, and on the other hand, it can also bring a better feel to the user. The most important characteristic of soft glue covering hard glue is the bonding effect between the soft glue and the hard glue. If the bonding is poor, it will lead to abnormalities such as degumming during use. The composition and properties of the soft glue play a vital role in the coating effect. At present, there are a large number of patents that describe TPE, TPV, and TPU materials with good coating effects. In fact, in addition to the role of the soft glue, the coatability of the hard glue part also has a great influence on the final coating effect.

[0004] At present, with the large-scale, complex and diversified product structure design, the requirements for product performance are gradually increasing, and the products designed with soft glue coated with hard glue are gradually increasing in various fields. Therefore, we need to develop a polyamide composition with excellent coatability. Summary of the invention

[0005] The object of the present invention is to provide a polyamide composite material that is easily coated with soft glue, and a preparation method and application thereof.

[0006] The present invention is achieved through the following technical solutions:

[0007] A polyamide composite material comprises the following components by weight: 100 parts of polyamide with a terminal amino value of 45-200 mmol / kg and 0.1-8 parts of epoxy resin with an epoxy value of 0.03-0.3.

[0008] Preferably, the content of epoxy resin is 0.3-3 parts by weight;

[0009] More preferably, the content of the epoxy resin is 1.4-2.3 parts by weight.

[0010] Preferably, the terminal amino value of the polyamide is 85-150 mmol / kg.

[0011] Preferably, the epoxy value of the epoxy resin is 0.08-0.18.

[0012] The epoxy value of epoxy resin is used to characterize the amount of epoxy group contained in every 100g of epoxy resin, and its unit is mol / 100g;

[0013] The epoxy resin is selected from at least one of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bromine-containing epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, biphenyl epoxy resin, tetramethyl diphenyl epoxy resin, cresol novolac epoxy resin, phenol novolac epoxy resin, bisphenol A novolac epoxy resin, alicyclic epoxy resin and aliphatic epoxy resin;

[0014] Bisphenol A type epoxy resin is preferred.

[0015] The polyamide is selected from at least one of aliphatic polyamide and semi-aromatic polyamide. The aliphatic polyamide is a polyamide formed by condensation of at least one aliphatic dicarboxylic acid and at least one aliphatic diamine and / or a polyamide formed by condensation of at least one amino acid or at least one lactam with itself, including at least one of PA46, PA56, PA510, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA6, PA7, PA11, and PA12; the semi-aromatic polyamide is a polyamide formed by condensation of at least one aromatic dicarboxylic acid and at least one aliphatic diamine, and is selected from at least one of PA10T, PA10T1010, PA10T66, PA MXD6, PA MXD10, PA66 / 6T, PA6T, PA9T, and PA10T / 66;

[0016] Preferably, the polyamide is selected from aliphatic polyamide. The invention also comprises 0-200 parts of filler by weight; the filler is selected from at least one of fibrous filler and granular filler; the fibrous filler is selected from at least one of glass fiber, carbon fiber and basalt fiber; the granular filler is selected from at least one of alumina, carbon black, aluminosilicate clay, montmorillonite, zirconium phosphate, kaolin, calcium carbonate, diatomaceous earth, graphite, mica, silica, titanium dioxide, zeolite, talc, wollastonite and glass microspheres.

[0017] Whether to add 0-3 parts of auxiliary agents can be determined according to actual needs. The auxiliary agents are selected from antioxidants, lubricants, weathering agents, and nucleating agents.

[0018] The antioxidant may be a hindered phenol antioxidant, an alkali metal or alkaline earth metal hypophosphite, a phosphite antioxidant, etc.;

[0019] The lubricant can be a higher fatty acid, a higher fatty acid metal salt, a higher fatty acid ester or a higher fatty acid amide, etc.;

[0020] Weathering agents can be salicylate, benzotriazole and benzophenone, secondary amine stabilizers, tertiary amine stabilizers, NOR stabilizers, etc.

[0021] The nucleating agent can be a higher fatty acid metal salt, nano metal particles, etc.

[0022] The preparation method of the polyamide composite material of the present invention comprises the following steps: mixing the components uniformly, feeding the components into a twin-screw extruder through a main feeding port for extrusion granulation, wherein the screw barrel temperature ranges from 180 to 300° C., the screw aspect ratio is 36 to 52:1, the rotation speed is 200 to 700 rpm, and if a filler is side-fed, a polyamide composite material is obtained.

[0023] The polyamide composite material of the present invention is used for preparing a product coated with soft glue.

[0024] Nylon TPE and TPV packaging materials in the industry contain maleic anhydride. The present invention can improve the surface activity of polyamide composite materials through the synergy of polyamide resin with specific terminal amino content and epoxy resin with specific epoxy value, and react with maleic anhydride in the packaging material to significantly improve the bonding effect between the polyamide composite material and conventional polyamide encapsulation soft glue, which can be TPE, TPV, TPU material. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0026] The sources of raw materials used in the embodiments and comparative examples are as follows:

[0027] PA66-A: terminal amino content 47mmol / kg, EP-158, Zhejiang Huafeng;

[0028] PA66-B: terminal amino content 85mmol / kg, EP158NH, Zhejiang Huafeng;

[0029] PA66-C: terminal amino content 110mmol / kg, EP126NH, Zhejiang Huafeng;

[0030] PA66-D: terminal amino content 180mmol / kg, provided by Zhejiang Huafeng;

[0031] PA66-E: terminal amino content 24mmol / kg, EPR32, Henan Shenma;

[0032] PA6-A: terminal amino content 64mmol / kg, H35ZI, Honeywell;

[0033] PA6-B: terminal amino content 23mmol / kg, M2000, Xinhui Meida;

[0034] PA610: terminal amino content 51mmol / kg, PA610 F120, Shandong Guangyin;

[0035] PA1010: terminal amino content 47mmol / kg, PA1010, Wuxi Yinda Nylon Co., Ltd.;

[0036] PAMXD10: terminal amino content 46mmol / kg, PAMXD10, Shanghai Yinggu; PA66 / 6T: terminal amino content 48mmol / kg, C1504T, Shandong Guangyin;

[0037] Glass fiber: ECS301HP-3-H, CPIC;

[0038] Talc: AH-1250N6, Guangxi Longsheng Huamei;

[0039] Epoxy resin A: Epoxy value is 0.030-0.042, bisphenol A type, brand name YD-019, manufacturer Dongdu Chemical;

[0040] Epoxy resin B: Epoxy value is 0.100-0.111, bisphenol A type, brand name YD-014, manufacturer: Dongdu Chemical;

[0041] Epoxy resin C: Epoxy value is 0.143-0.167, bisphenol A type, brand name YD-012, manufacturer Dongdu Chemical;

[0042] Epoxy resin D: Epoxy value is 0.200-0.222, bisphenol A type, brand name YD-011, manufacturer: Dongdu Chemical;

[0043] Epoxy resin E: Epoxy value is 0.017-0.025, bisphenol A type, brand name YD-020, manufacturer Dongdu Chemical;

[0044] Epoxy resin F: Epoxy value is 0.370-0.435, bisphenol A type, brand name YD-134, manufacturer: Dongdu Chemical;

[0045] Epoxy resin G: Epoxy value is 0.048-0.057, bisphenol F type epoxy resin, brand name YDF-2007, manufacturer: Dongdu Chemical;

[0046] Epoxy resin H: Epoxy value is 0.091-0.111, hydrogenated bisphenol A type epoxy resin, brand ST-5100, manufacturer Dongdu Chemical;

[0047] Epoxy resin I: Epoxy value is 0.200-0.222, bromine-containing epoxy resin, brand name YDB-715, manufacturer: Dongdu Chemical;

[0048] Ethylene-butyl acrylate-glycidyl methacrylate copolymer: PTW, DuPont, USA;

[0049] Ethylene-methyl acrylate-glyceryl methacrylate copolymer: AX8900, Arkema, France;

[0050] Ethylene-butyl acrylate-glycidyl methacrylate grafted polyolefin elastomer: SOG-03, Jiangsu Jiayirong.

[0051] The preparation method of the polyamide composition of the embodiments and comparative examples is as follows: the other components except the glass fiber are mixed uniformly, and the components are fed into a twin-screw extruder through the main feeding port for extrusion granulation. The screw aspect ratio is 40:1, the barrel temperature segmentation is 260 / 260 / 250 / 240 / 230 / 230 / 230 / 240 / 260°C, and the screw speed is 300 rpm. If glass fiber or talcum powder is side-fed, a polyamide composition is obtained.

[0052] Test method:

[0053] (1) Dry-state encapsulation test: Two soft-gel materials were selected for evaluation, including TPE and TPV materials commonly used in the market for nylon coating. The evaluation was performed using a soft-gel encapsulated hard-gel mold. First, the polyamide composition prepared in the above embodiment and comparative example was used to injection mold a polyamide rectangular plate with a length of 200 mm, a width of 50 mm, and a thickness of 2.5 mm. The rectangular plate was left to cool for 24 hours. The mold surface was replaced with a soft-gel injection mold, and the molded rectangular plate was embedded in the movable mold surface. The soft-gel part was further injection molded, including 10 groups of samples of TPE and TPV soft gel. The product of the soft gel bonded polyamide rectangular plate hard gel was left to cool for 24 hours for subsequent bonding strength testing.

[0054] The above-mentioned soft adhesive bonded to hard adhesive products were tested using a specially modified adhesion tester. The equipment was built with reference to the test method for tear resistance (cut tear) of plastic film and sheet of ASTM D1004-07. During the test, the hard adhesive part was fixed and the soft adhesive part was clamped. The tensile tear test was carried out at a speed of 50 mm / min until the soft adhesive broke or the soft adhesive and the hard adhesive were completely separated. The test was ended. The separation of the soft adhesive and the hard adhesive was observed. The judgment criteria were as follows:

[0055] Comparison of lagging effect levels:

[0056] Level 1: There is no obvious separation between the soft and hard adhesive parts until the soft adhesive is torn or broken; or the soft adhesive is completely torn, but the surface of the hard adhesive is covered with residual soft adhesive and no separation occurs; excellent adhesion is shown;

[0057] Level 2: Until the soft rubber is torn or broken, there is only very slight separation between the soft rubber and the hard rubber, and the separation area accounts for less than 5% of the total rubber lagging area; it shows good adhesion;

[0058] Level 3: Until the soft rubber is torn or broken, the soft rubber and hard rubber are obviously separated, and the separation area accounts for 5-20% of the rubber lagging area; it shows qualified adhesion;

[0059] Level 4: Until the soft rubber is torn or broken, the soft rubber and hard rubber are obviously separated, and the separation area accounts for 20-80% of the rubber lagging area; showing poor adhesion;

[0060] Level 5: Until the soft glue is torn or broken, the soft and hard glue are obviously separated, the separation area accounts for more than 80% of the rubber coating area or is completely peeled off; showing very poor adhesion.

[0061] Table 1: Contents of components (parts by weight) and test results of polyamide compositions of Examples 1-7

[0062] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 PA66-A 100 100 PA66-B 100 PA66-C 100 PA66-D 100 PA6-A 100 PA610 100 Fiberglass 60 60 60 60 60 60 talcum powder 60 Epoxy resin B 1.5 1.5 1.5 1.5 1.5 1.5 1.5 TPE-coated polyamide hard plastic, grade Level 1 Level 1 Level 1 Level 2 Level 1 Level 1 Level 1 TPV coated polyamide hard glue, grade Level 2 Level 1 Level 1 Level 2 Level 2 Level 2 Level 2

[0063] It can be seen from Examples 1-7 that the polyamide composite material of the present invention has excellent encapsulation properties.

[0064] Table 2: Content of each component (parts by weight) and test results of polyamide compositions of Examples 8-13

[0065] Example 8 Example 9 Example 10 Embodiment 11 Example 12 Example 13 PA66-A 100 100 100 100 100 100 Fiberglass 60 60 60 60 60 60 Epoxy Resin A 1.5 Epoxy resin C 1.5 Epoxy resin D 1.5 Epoxy resin G 1.5 Epoxy Resin H 1.5 Epoxy Resin I 1.5 TPE-coated polyamide hard plastic, grade Level 2 Level 1 Level 2 Level 2 Level 2 Level 2 TPV coated polyamide hard glue, grade Level 2 Level 2 Level 2 Level 3 Level 2 Level 3

[0066] It can be seen from Examples 1 / 8-13 that the preferred epoxy resin type is bisphenol A type, and the preferred epoxy value is 0.08-0.18.

[0067] Table 3: Content (parts by weight) of each component of the polyamide composition of Examples 14-19 and test results

[0068] Embodiment 14 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 PA66-A 100 100 100 100 100 100 Fiberglass 60 60 60 60 60 10 Epoxy resin B 0.1 0.3 2.3 3 8 1.5 TPE-coated polyamide hard plastic, grade Level 2 Level 2 Level 1 Level 2 Level 2 Level 1 TPV coated polyamide hard glue, grade Level 3 Level 2 Level 2 Level 2 Level 3 Level 2

[0069] It can be seen from Examples 1 / 14-19 that the encapsulation property is better under the preferred range of epoxy resin addition.

[0070] Table 4: Content (parts by weight) of each component of the polyamide composition of Examples 20-22 and test results

[0071] Embodiment 20 Embodiment 21 Embodiment 22 PA1010 100 PAMXD10 100 PA66 / 6T 100 Fiberglass 60 60 60 Epoxy resin B 1.5 1.5 1.5 TPE-coated polyamide hard plastic, grade Level 1 Level 2 Level 2 TPV coated polyamide hard glue, grade Level 2 Level 2 Level 2

[0072] It can be seen from Examples 1 / 5 / 6 / 22-26 that aliphatic polyamide is preferred for better encapsulation properties.

[0073] Table 5: Content of each component (parts by weight) and test results of the polyamide compositions of Comparative Examples 1-7

[0074] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 PA66-A 100 100 100 100 100 PA66-E 100 PA6-B 100 Fiberglass 60 60 60 60 60 60 60 Epoxy resin B 1.5 1.5 Epoxy Resin E 1.5 Epoxy resin F 1.5 Ethylene-butyl acrylate-glycidyl methacrylate copolymer 1.5 Ethylene-methyl acrylate-glyceryl methacrylate copolymer 1.5 Ethylene-butyl acrylate-glycidyl methacrylate grafted polyolefin elastomer 1.5 TPE-coated polyamide hard plastic, grade Level 3 Level 3 Level 3 Level 4 Level 4 Level 3 Level 4 TPV coated polyamide hard glue, grade Level 4 Level 4 Level 3 Level 4 Level 4 Level 4 Level 4

[0075] It can be seen from Comparative Examples 1 / 2 that when the terminal amino group of the aliphatic polyamide resin is less than 45 mmol / kg, the encapsulation property is poor.

[0076] It can be seen from Comparative Examples 3-7 that when the epoxy value of the epoxy resin is not within the scope of the present invention, or other epoxy group-containing polymers are selected, it is not possible to effectively achieve a significant improvement in encapsulation properties.

[0077] Table 6: Content of each component (parts by weight) and test results of the polyamide compositions of Comparative Examples 8-9

[0078] Comparative Example 8 Comparative Example 9 PA66-A 100 100 Fiberglass 60 60 Epoxy resin B 0.01 10 TPE-coated polyamide hard plastic, grade Level 4 Level 3 TPV coated polyamide hard glue, grade Level 5 Level 4

[0079] It can be seen from Comparative Examples 8-9 that when the amount of epoxy resin added is too much or too little, the encapsulation property is poor.

Claims

1. A polyamide composite material, characterized in that: The invention comprises the following components by weight: 100 parts of polyamide with a terminal amino value of 45-200 mmol / kg, and 0.3-3 parts of epoxy resin with an epoxy value of 0.03-0.3; the epoxy resin is selected from at least one of bisphenol A epoxy resin and hydrogenated bisphenol A epoxy resin; the polyamide is selected from at least one of aliphatic polyamide and semi-aromatic polyamide.

2. The polyamide composite material according to claim 1, characterized in that: The weight content of the epoxy resin is 1.4-2.3 parts by weight.

3. The polyamide composite material according to claim 1, characterized in that: The terminal amino value of the polyamide is 85-150 mmol / kg.

4. The polyamide composite material according to claim 1, characterized in that: The epoxy value of epoxy resin is 0.08-0.

18.

5. The polyamide composite material according to claim 1, characterized in that: The epoxy resin is selected from bisphenol A epoxy resin.

6. The polyamide composite material according to claim 1, characterized in that: The aliphatic polyamide is a polyamide formed by condensation of at least one aliphatic dicarboxylic acid and at least one aliphatic diamine and / or a polyamide formed by condensation of at least one amino acid or at least one lactam with itself, including at least one of PA46, PA56, PA510, PA66, PA610, PA612, PA1010, PA1012, PA1212, PA6, PA7, PA11, and PA12; the semi-aromatic polyamide is a polyamide formed by condensation of at least one aromatic dicarboxylic acid and at least one aliphatic diamine, and is selected from at least one of PA10T, PA10T1010, PA10T66, PA66 / 6T, PA6T, PA9T, and PA10T / 66.

7. The polyamide composite material according to claim 1, characterized in that: The polyamide is selected from aliphatic polyamide.

8. The polyamide composite material according to claim 1, characterized in that: The polyamide is selected from at least one of PA MXD6 and PAMXD10.

9. The polyamide composite material according to claim 1, characterized in that: By weight, it also includes 0-60 parts of filler; the filler is selected from at least one of fibrous fillers and granular fillers; the fibrous filler is selected from at least one of glass fiber, carbon fiber, and basalt fiber; the granular filler is selected from at least one of alumina, carbon black, aluminosilicate clay, montmorillonite, zirconium phosphate, kaolin, calcium carbonate, diatomaceous earth, graphite, mica, silica, titanium dioxide, zeolite, talc, wollastonite, and glass beads.

10. The polyamide composite material according to claim 1, characterized in that: The invention also includes 0-3 parts of auxiliary agents by weight, wherein the auxiliary agents are selected from at least one of antioxidants, lubricants, weathering agents and nucleating agents.

11. The method for preparing the polyamide composite material according to any one of claims 1 to 10, characterized in that: The method comprises the following steps: mixing the components uniformly, feeding the components into a twin-screw extruder through a main feeding port for extrusion granulation, wherein the aspect ratio of the screw is 36-52:1, the temperature range of the screw barrel is 180-300°C, the rotation speed is 200-700rpm, and if a filler is side-fed, a polyamide composite material is obtained.

12. Use of the polyamide composite material according to any one of claims 1 to 10, characterized in that: Used to prepare parts covered with soft rubber.

Citation Information

Patent Citations

  • Highly-heatproof polyamide composition and preparation method thereof

    CN110229515A

  • Curable resin composition, use thereof, and production method thereof

    CN113214778A